Analysis of the Investment Value of New Energy Vehicle Enterprises Based on the Analysis of Barringer/Ireland Business Model - Chen, Cheng (International Journal of Global Economics and Management, 2024)
The purpose of this report is to decide which company between Xpeng or Nio to invest in based on the analysis of Barringer/Ireland Business Model. Firstly, according to the research and data collection, the report briefly introduces the general situation and development of the new energy vehicle market and the background of the two companies Xpeng and Nio. Then, through the reliable and real information of Xpeng and Nio, the report applies all 12 parts of the theory to Xpeng and Nio, and analyzes the advantages and disadvantages of these two companies in these 12 factors. Thirdly, the two companies are compared based on theoretical analysis of 12 factors in Barringer/Ireland Business Model. Finally, the report figures out which company to invest in, and speculates and analyzes the future development trend of this company according to analysis of Barringer/Ireland Business Model. All in all, the whole report is completed based on numbers of reliable and real data, analysis of articles and researches.